Desarrollo de un inversor trifásico con modulación SPWM e interfaz gráfica para el Laboratorio de Electrónica de Potencia - Reyes Pérez, Cristian Xavier (2018)
The project presents the construction of a didactic module of a three-phase inverter with SPWM modulation and graphic interface, which allows the variation frequency and amplitude of the inverter. A fully controlled single phase rectifier is implemented, with SCR's and controlled by an Arduino Uno, which sends the times of activation and deactivation of the SCR's for the control of the firing angle and thus modify the amplitude or the voltage that will enter the three-phase inverter. The three-phase inverter bridge is developed using IGBT's and controlled by the SPWM modulation that was generated when comparing a carrier signal and a modulating signal. The activation and deactivation of the IGBT's is doing through an Arduino Mega that also controls the variation of the frequency of the three-phase inverter. An HMI is making with a Nextion screen and a controller that allows the sending of the data to modify the amplitude and frequency. The acquisition of motor speed data is making with the Hall Effect sensor and the motor speed value is showing on the Nextion screen. Connections are installing in the didactic module that allows obtaining the signals to be visualize in an external oscilloscope. The signals are for control of the IGBT's, the rectified signal and the three-phase RST signals. In addition, it can be connect to the loads of the Power Electronics Laboratory of the UPS. The data provided by the module allows the experimental behavior of the three-phase inverter to be studied using SPWM modulation.